Epstein Barr Virus Associated B-Cell Lymphomas and Iatrogenic Lymphoproliferative Disorders - Crombie, Jennifer L.; LaCasce, Ann S. (Frontiers in Oncology, 2019)
Epstein-Barr virus (EBV) is a ubiquitous herpesvirus, affecting up to ninety percent of the population. EBV was first identified as an oncogenic virus in a Burkitt lymphoma cell line, though subsequently has been found to drive a variety of malignancies, including diffuse large B-cell lymphoma (DLBCL) and other lymphoma subtypes. EBV has a tropism for B-lymphocytes and has the unique ability to exist in a latent state, evading the host immune response. In cases of impaired cell mediated immunity, as in patients with advanced age or iatrogenic immune suppression, the virus is able to proliferate in an unregulated fashion, expressing viral antigens that predispose to transformation. EBV-positive DLBCL not otherwise specified, which has been included as a revised provisional entity in the 2016 WHO classification of lymphoid malignancies, is thought to commonly occur in older patients with immunosenescence. Similarly, it is well established that iatrogenic immune suppression, occurring in both transplant and non-transplant settings, can predispose to EBV-driven lymphoproliferative disorders. EBV-positive lymphoproliferative disorders are heterogeneous, with variable clinical features and prognoses depending on the context in which they arise. While DLBCL is the most common subtype, other histologic variants, including Burkitt lymphoma, NK/T-cell lymphoma, and Hodgkin lymphoma an occur. Research aimed at understanding the underlying biology and disease prevention strategies in EBV-associated lymphoproliferative diseases are ongoing. Additionally, personalized treatment approaches, such as immunotherapy and adoptive T-cell therapies, have yielded encouraging results, though randomized trials are needed to further define optimal management.